Alcune osservazioni su cristianesimo e nichilismo nella filosofia dell'ultimo Vattimo - Bonetti, Paolo (Bollettino Filosofico, 2015)
On his return to Christianity with Belief, Gianni Vattimo follows the tracks of Nietzsche and examines the relationship between nihilism and Christian theology. The philosopher turns again to faith, using the theoretical instruments peculiar to hermeneutics. What results is an ethic of non-violence, maintained by Vattimo through a burst of charity.